A Analysis of High School Students' Scientific Attitudes in Biology Learning: A Literature Study - Qanzha Qanzha; Heffi Alberida; Rahmawati D. (LP2M UIN Ambon, 2026)
Scientific attitude is an essential competence in Biology learning that needs to be developed to support students’ scientific thinking processes. This study aims to analyze the scientific attitudes of senior high school students in Biology learning through a literature study. The review was conducted on scientific articles published between 2010 and 2026, obtained from Google Scholar and ERIC databases using the keywords “scientific attitude” and “Biology learning.” The results show that students’ scientific attitudes include curiosity, critical thinking, objectivity, open-mindedness, accuracy, and collaboration in scientific activities. In general, students’ scientific attitudes are categorized as moderate, with curiosity as the most dominant aspect, while creativity and accuracy still need improvement. Factors influencing students’ scientific attitudes include learning models, learning environment, and the teacher’s role in facilitating scientific activities.